Just stories?: Epistemic (in)justice and everyday resistance in the digital stories of family literacy practices by Grade 1-5 workers at a South African University - Viedge, Jane Margaret (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This thesis sets out to establish in what ways digital storytelling (DST) revealed instances of epistemic (in)justices inherent in the family literacy intervention experiences of four Black, working-class parents employed at a South African University1. Additionally, it explores how DST might be used by the participants (self-labelled the Storytelling Family Literacy - SFL Advocates) to correct any harm done. The context for the research is based on the deep-rooted harms of Bantu education in which Black South Africans were denied equal access to resources such as literacy practices. I investigated these aims by using the theories of DST, Communication for Social Change (C4SC) and epistemic (in)justice. As a participatory media practice supporting communications in marginalised communities, DST's broad purpose is to assist these communities in telling stories of their lived experiences in ways that change dominant and, therefore, unchallenged views about them (Servaes & Malikhao 2014). In facilitating DST workshops with the SFL Advocates, I searched for evidence of epistemic (in)justice to enhance our (all stakeholders) understanding of their literacy experiences in ways that addressed their credibility status as 'knowers' (Fricker, 2007). Viewed through this lens, utilising DST provided a mechanism for understanding the impact of social interventions in a university setting that aimed to correct past injustices. The process involved online and face-to-face workshops with the participants during the Covid-19 Lockdown. The online format hampered data collection processes, and I resorted to face-to-face interactions for the workshops and interviews. These interactions were distinctly different from those I had experienced with participants in previous workshops, and they became a key focus in my analysis. Using narrative inquiry with critical realist and interpretive analysis techniques to interrogate the data, I discovered DST has both weaknesses and strengths as a C4SC communication tool. My findings revealed participants who, in the moment of leading their children and communities through the family literacy intervention, could claim to have redressed epistemic harms from the legacy of Apartheid education. However, by reflecting on this moment, the participants brought to light an epistemic harm that had been previously left unspoken: their sense of restored credibility as knowledge-bearers during the intervention was deeply shaken when the programme ended because they felt abandoned by the university. Therefore, the epistemic (in)justice lens unveiled hidden injustices that curtailed the participants' ability to participate fully in the DST workshops. They described suffering the effects of pernicious and arbitrary acts of epistemic injustice at the hands of the University. Their participation in my workshops was erratic, and their stories were incomplete. As a result, I experienced difficulty analysing what I perceived as a lack of data. Moreover, despite my independent researcher status, my positionality as participant-observer was problematic as the participants may have perceived me as representative of the University and its institutional power. I responded to the problematic data by including a new theoretical framework in my analysis: the theory of everyday resistance (Vinthagen & Johansson, 2013). Combined with epistemic (in)justice theory and Vivienne's ideas of using DST for everyday activism, I theorised how the participants negotiated their expressions of identity in epistemically unjust spaces. To put institutional epistemic injustice in perspective in the context of the University, I drew on Fricker's three models of epistemic justice that enable fair and free conditions for marginalised workers to communicate for social change.
Keywords: Digital storytelling; Family literacy programs; Epistemic injustice; Epistemic justice; Communication for social change; Fricker, Miranda